Biodiversity and Updated Systematic Checklist of Leafhoppers, Treehoppers and Planthoppers (Auchenorrhyncha : Hemiptera) of Jammu & Kashmir, India - Bhagat, R. C. (Indian Forester, 2017)
The present paper deals with Auchenorrhyncha- fauna (Leafhoppers, treehoppers and planthoppers), covering 94 species, belonging to 63 genera, occurring in diverse areas and localities of Jammu and Kashmir regions of Indian sub-continent. These species pertain to Infra-order Cicadomorpha, Superfamily Membracoidea, family Cicadellidae, Membracidae and, Infra-order Fulgoromorpha, Superfamily Fulgoroidea, family Delphacidae and Derbidae. The Cicadellidae has been found to be dominant family, with 9 sub-families and 10 tribes, including 84 species under 57 genera. This family in dominance, is followed by Membracidae, with 7 spp. (3 genn.) and, Delphacidae and Derbidae, with 2 spp. (2 genn.) and 1 sp. (1 gen.) respectively. The taxa have been updated in the light of recent nomenclatural / systematic changes. About 18 species of host- plants, including agricultural crops and economically important plant species, belonging to 12 families, are damaged by 31 spp. of Auchenorrhyncha. An up-to-date systematic annotated checklist has been provided. In addition to this, faunal distribution and biodiversity, have briefly been discussed.